Intracellular localization of gold nanoparticles with targeted delivery in MT-4 lymphocytes. (13th October 2016) - Singh, Lavanya; Parboosing, Raveen; Kruger, Hendrik G; Maguire, Glenn E M; Govender, Thavendran
Abstract: The clinical utility of important therapeutic agents is often limited by the poor permeability of biological membranes. Cell penetrating peptides are usually employed to circumvent this challenge. This approach, coupled with gold nanoparticles, are a promising vehicle for drug delivery due to its good biocompatibility profile, negligable toxicity and possibility for multi-functionalization. Here we report the functionalization and intracellular tracking of gold nanoparticles decorated with a TAT cell penetrating peptide and a fluorescein tag in a simple, two step process. Fluorescence microscopy has confirmed the localization of the functionalized nanoparticles to be inside the cells, specifically within, or in close proximity to the nuclei of MT-4 lymphocytes; a HIV-relevant cell line in which this has not been previously demonstrated. The results of this study demonstrate that TAT has been efficiently conjugated to gold nanoparticles to facilitate both cellular and targeted nuclear entry.